2016
DOI: 10.1155/2016/5701609
|View full text |Cite
|
Sign up to set email alerts
|

Are Patients with Polycystic Ovarian Syndrome Ideal Candidates for Oocyte Donation?

Abstract: Background. The use of donated oocytes for in vitro fertilization treatment in patients with ovarian failure is universally recognized. But would patients with polycystic ovarian syndrome (PCOS) be a good choice for egg donation programs? Objective. Comparing the pregnancy rates of egg receptors from donor patients diagnosed with PCOS to receptors from donors without PCOS. Design. Retrospective cohort study. Methods. A total of 234 patients who had undergone egg reception program were separated into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Since oocytes and embryo quality do not seems to be the cause of low implantation and pregnancy rate in PCOS patients as demonstrated by donor oocyte models [19,20], the decreased receptivity of the endometrium seems more probable. Indeed, accumulating data support the hypothesis that endometrium of PCOS patients is affected probably as a consequence of hormonal imbalance.…”
Section: Fertility In Patients With Polycystic Ovary Syndromementioning
confidence: 99%
“…Since oocytes and embryo quality do not seems to be the cause of low implantation and pregnancy rate in PCOS patients as demonstrated by donor oocyte models [19,20], the decreased receptivity of the endometrium seems more probable. Indeed, accumulating data support the hypothesis that endometrium of PCOS patients is affected probably as a consequence of hormonal imbalance.…”
Section: Fertility In Patients With Polycystic Ovary Syndromementioning
confidence: 99%
“…Ovulation disorders/anovulation is an important cause of PCOS-related infertility,affecting 40% of women of reproductive age all over the world [2]. With the development of technology,PCOS patients can obtain highquality fertilized eggs with assisted reproductive technology(ART).However,studies found that the success rate of transplantation are lower and the spontaneous abortion are higher among the women with PCOS comparing to non-PCOS patients [3][4].Unexpectedly,using the oocytes donated by PCOS women will not lower fertilization,implantation and clinical pregnancy rates [5].Several pathophysiological changes in PCOS,like oligomenorrhea,hyperandrogen -ism, hyperinsulinemia, abnormal luteinizing hormone (LH) secretion and in ammation has been con rmed to compromise endometrial health in the long term,including dysfunctional endometrial receptivity(ER) [6][7].Endometrial receptivity refers to the status of the uterus when the endometrium is in synchrony with development of the blastocyst and is available to accept the blastocyst for adhesion, invasion and implantation [8].The decrease of endometrial receptivity is one of the most important causes of infertility or pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%
“…The article “Are Patients with Polycystic Ovarian Syndrome Ideal Candidates for Oocyte Donation?” by Vaz et al [ 1 ] is important because IVF (in vitro fertilization) offers hope to millions of infertile couples. The demand and use of donated oocytes have increased significantly over the last decade.…”
mentioning
confidence: 99%